2013
DOI: 10.1186/1472-6882-13-327
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of blood perfusion coherence along the meridian in forearm

Abstract: BackgroundMany studies have explored the relationship between skin microcirculation and meridian activation. However, few studies have examined blood perfusion coherence along the meridians, and other studies have suggested that the skin vasodilator response relates to age. This study investigated blood perfusion coherence characteristics along the meridian of the forearm in healthy volunteers.MethodsA total of 15 young subjects (25.53 ± 2.20) and 15 middle-aged subjects (50.07 ± 3.37) were recruited for this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Coherence analysis is a method to estimate the correlation of the signals on different frequencies, which can be used for analysis correlation of two blood flux signals in frequency domain [ 24 26 ]. In the previous study, the coherence analysis along PC meridian was carried out in different aged human before and after 30 mmHg inflating occlusion [ 27 ]. Further study indicated that coherence analysis might be used to assess microcirculatory changes at different ages [ 28 ] and oral load different cold water [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Coherence analysis is a method to estimate the correlation of the signals on different frequencies, which can be used for analysis correlation of two blood flux signals in frequency domain [ 24 26 ]. In the previous study, the coherence analysis along PC meridian was carried out in different aged human before and after 30 mmHg inflating occlusion [ 27 ]. Further study indicated that coherence analysis might be used to assess microcirculatory changes at different ages [ 28 ] and oral load different cold water [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Coherence analysis is a method to analysis correlation of two blood flux signals in frequency domain [42]. In previous study, we observed that 30 mmHg inflating occlusion resulted in change of coherence values in middle-aged subjects in special frequency bands; however, the same stimulus did not change the coherence value in young-aged subjects [43] in the same band. Further study indicated that coherence analysis might provide a potential noninvasive method to assess microcirculatory changes in different ages [44].…”
Section: Discussionmentioning
confidence: 99%
“…With references to similar studies ( Hsiu et al, 2007 ; Wang et al, 2013 ; Jo and Kim, 2016 ) in this field and our previously published study ( Lou et al, 2020 ), the establishment of examination conditions was described in detail as follows. One week before examinations, all subjects refrained from medications that could affect microcirculation and vasoreactivity for 1 week.…”
Section: Methodsmentioning
confidence: 99%